Review of SMS based agro-advisories in India: ingredients for success for decisions around climate risk management in farming. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
ICT enabled climate services information linked to agro-advisories have directly enabled more than 5,000 farmers in at least 10 districts in India (since 2016) to make better decisions in planning and managing their farms using SMS delivered context specific, agro-advisories that incorporate medium-, extended-range and seasonal climate forecasts. This will likely to result in 20% increase in the yield of groundnut and chickpea crops and contribute US$225/hectare to income.